Tourism : Student's book Level 1 - Walker, Robin; Harding, Keith (United Kingdom Oxford University Press, 2006)
Tourism is divided into three levels: Provision, encounters, and management. Each of these levels develops the vocabulary, language, and skills that students will need to communicate effectively with customers and colleagues, whether working in an administrative or managerial role.
Keywords: Cơ bản